2018
DOI: 10.1371/journal.pone.0197213
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center preclinical study of gadoxetate DCE-MRI in rats as a biomarker of drug induced inhibition of liver transporter function

Abstract: Drug-induced liver injury (DILI) is a leading cause of acute liver failure and transplantation. DILI can be the result of impaired hepatobiliary transporters, with altered bile formation, flow, and subsequent cholestasis. We used gadoxetate dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), combined with pharmacokinetic modelling, to measure hepatobiliary transporter function in vivo in rats. The sensitivity and robustness of the method was tested by evaluating the effect of a clinical dose of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…In hepatocellular carcinoma patients, one study showed an increased accumulation of gadoxetate in the tumor cells due to an increase in OATP1B1 and OATP1B3 expression and a decrease in MRP2 expression relative to healthy liver tissue [130]. DCE-MRI with gadoxetate has also been used in DDI studies in mice and rats, in which novel MRI quantification methods showed a reduction in the uptake and efflux rates of gadoxetate after treatment with rifampicin [131,132].…”
Section: Mri Contrast Agents To Study Liver Transportersmentioning
confidence: 99%
“…In hepatocellular carcinoma patients, one study showed an increased accumulation of gadoxetate in the tumor cells due to an increase in OATP1B1 and OATP1B3 expression and a decrease in MRP2 expression relative to healthy liver tissue [130]. DCE-MRI with gadoxetate has also been used in DDI studies in mice and rats, in which novel MRI quantification methods showed a reduction in the uptake and efflux rates of gadoxetate after treatment with rifampicin [131,132].…”
Section: Mri Contrast Agents To Study Liver Transportersmentioning
confidence: 99%
“…The first approach, using what is called the Patlak model (Figure 6.4; Patlak model), uses a simple two-compartment model and estimates the gadoxetate uptake and efflux rates. The Patlak model uses an input function sampled in the blood [116,117] or spleen [118,119]. The model then assumes that the blood extracellular concentration in the liver is the same as the concentration in the blood, which is the same thing as assuming that the mean transit time och the contrast agent in the extracellular space is considered negligible.…”
Section: Patlak Modelmentioning
confidence: 99%
“…Several different studies have investigated modeling of gadoxetate-enhanced MRI as a biomarker for DILI. Initially, Ulloa et al used the Patlak model to study the effects of a hepatotoxic drug, [118] and this approach was later applied and verified in a multi-center study [119]. A similar approach was also tested by Georgiou et al [151].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…[5][6][7] Specific uptake of gadoxetate by hepatocytes leads to T1-shortening of liver parenchyma, while liver lesions show characteristic signal deviation from the parenchyma, thus contrasting the lesions. Genetic factors, 8 chronic liver diseases 9 and drug-drug interactions 10,11 may affect gadoxetate transport through hepatocytes, influencing liver parenchyma enhancement.…”
Section: Introductionmentioning
confidence: 99%